CONSUMER BEHAVIOUR TRENDS AND EVOLUTION IN FASHION RETAIL: A STUDY IN VELLORE DISTRICT - 1. M. JANANI , 2. Dr. S. HARIHARAN (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
The fashion retail industry is undergoing rapid transformation, driven by evolving consumer preferences, digital influence, and changing lifestyles. This study explores the trends and evolution of consumer behaviour in the fashion retail sector in Vellore District, a region experiencing both traditional and modern retail growth. It focuses on key behavioural factors such as brand preference, shopping mode (online vs. offline), influence of advertisements, peer groups, pricing, and quality considerations. Using a structured questionnaire and statistical tools, the research highlights significant shifts in fashion buying patterns over recent years. Findings reveal that consumers are increasingly trend-conscious, brand-aware, and influenced by social media and promotional offers. The study offers valuable insights for retailers and marketers to tailor strategies in line with local consumer behaviour. It also emphasizes the growing importance of experience, digital presence, and personalized engagement in modern fashion retail.